Transformational Leadership and Project Success: The Role of Leader-Member Exchange and Professional Commitment - Thuy, Doan Thi Thanh (Emerging Science Journal, 2024)
The purpose of this study is to explore the effects of transformational leadership (TL) on project success (PS), focusing on the indirect impacts of leader-member exchange (LMX) and the moderating influence of professional commitment (PC). This study aims to address the inconsistent findings in existing literature regarding the transformational leadership-project success relationship and to uncover the mechanisms that affect project outcomes. The unit of analysis is finished projects. The 509 project managers on projects completed within the past five years responded to the poll to collect data. The data were then assessed using Smart-PLS software. The results confirmed the study’s hypotheses, demonstrating that LMX mediates the relationship between transformational leadership and project success. Additionally, professional commitment was found to moderate both the relationship between transformational leadership and LMX and the connection between LMX and project success. Furthermore, transformational leadership was shown to have a direct positive effect on project success. These findings contribute to the theoretical foundations of leadership and project management by emphasizing the critical role of relationship quality within teams, with LMX serving as an intervention mechanism and professional commitment acting as a moderating role influencing project success. The insights from this study offer practical value for developing project management strategies tailored to specific organizational contexts, enhancing efficiency in project-based organizations. Future research should consider longitudinal studies to explore how the relationships between these antecedents and project outcomes evolve over time. Doi: 10.28991/ESJ-2024-08-06-022 Full Text: PDF